559 Use of a risk assessment to promote farmer's health. (24th April 2018) - McNamara, J; Griffin, P; Phelan, J; Kinsella, J
Abstract : Introduction: Research in Ireland has indicated that farmers as an occupational group have inferior health outcomes. To assist with addressing this issue, health issues were included in a pilot Risk Assessment (RA) and associated half-day training course being evaluated for the agriculture sector under OSH legislation. The health RA template required a farmer to specify missing health controls. Farmers could complete the RA document with or without half-day training. At training guidance on health issues was provided using a DVD presented by a medical doctor. This paper provides evaluation on the health related controls specified in the RA for action and opinions of training provided. Methods: RA documents were obtained from farmers who completed it with (n=335) and without (n=140) training and health controls specified for action were tabulated. Opinions were obtained from both farmers (n=291) and trainers (n=51) on the health element of RA training delivered using a Likert-type question with a 5 point scale, with 5 the most positive response. Trainers had the option of additionally providing a comment. Results: A total of 0.32 and 0.14 controls per RA document were specified when completed with or without training. Controls were in the following categories: preventing back injury (2.4%); respiratory protection (9.5%), preventing infection (17.6%), noise exposure control (9.5%), stress/personal health management (56.4%) (obtaining a 1 st aid box made-up 80% of this category) and additional controls (4.8%). The opinion of health messages delivered at training had a mean score of 3.9 among both farmer and trainer respondents. Additionally 25.5% of trainers commented positively on the benefit of health training. Conclusion: The study indicates low uptake of health practices by farmers following RA completion. Training increased the level of specification of controls. Feedback from both farmers and trainers related to the health messages delivered at training was positive.